2022
DOI: 10.1021/acsomega.2c02884
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Deep-UV Photoluminescence from Low-Dimensional Hexagonal Boron Nitride Prepared Using a Facile Synthesis

Abstract: Identification and evaluation of defect levels in low-dimensional materials is an important aspect in quantum science. In this article, we report a facile synthesis method of low-dimensional hexagonal boron nitride (h-BN) and study light emission characteristics due to the defects. The thermal annealing procedure is optimized to obtain clean multilayered h-BN as revealed by transmission electron microscopy. UV–vis spectroscopy shows the optical energy gap of 5.28 eV, which is comparable to the reported energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…A gradually decrease of the optical bandgap by increasing the carbon content is reported in literature for exfoliated BN nanostructures. [38,39] Additionally, the optical bandgap at about E g2 = 4.2 eV is reasonably ascribable to carbon-substituted BNQDs as reported in literature [40,41] and recently by Thamankar and co-workers. [39] In summary, the red-shifted optical absorption bands above 350 nm observed for the BNQDs in comparison with the bare-BNs, undoubtedly supported the formation of carbon-functionalized BNQDs structures.…”
Section: Synthetic Strategy and Structure Of The Carbon-bnqdssupporting
confidence: 79%
“…A gradually decrease of the optical bandgap by increasing the carbon content is reported in literature for exfoliated BN nanostructures. [38,39] Additionally, the optical bandgap at about E g2 = 4.2 eV is reasonably ascribable to carbon-substituted BNQDs as reported in literature [40,41] and recently by Thamankar and co-workers. [39] In summary, the red-shifted optical absorption bands above 350 nm observed for the BNQDs in comparison with the bare-BNs, undoubtedly supported the formation of carbon-functionalized BNQDs structures.…”
Section: Synthetic Strategy and Structure Of The Carbon-bnqdssupporting
confidence: 79%
“…BN is a white, crystalline ceramic, commonly with a hexagonal crystal structure similar to that of graphite. Boron nitride has a wide range of applications, e.g ., lubricant, electrical insulators, thermal conductors, and deep ultraviolet (UV) emitter . Boron nitride is a well-known wide band gap semiconductor and has been successfully introduced for deep UV and neutron detection, benefiting from the decent charge transport properties (high sensitivity) and high resistivity (low noise level), making them ideal candidates for photodetection. For instance, Kaushik et al reported deep-ultraviolet photodetectors based on hexagonal boron nitride nanosheets and enhanced the device performance by localized surface plasmon resonance with Al nanoparticles . Liu and co-authors fabricated high-performance deep ultraviolet photodetectors based on few-layer hexagonal boron nitride and achieved ultra-high on/off ratio of >10 3 .…”
Section: Introductionmentioning
confidence: 99%